Kingdom of Lesotho : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
In this study, gross domestic product by sector and expenditure, consumer price indices, basic wages, public service employment, central government operations, government revenues and grants, southern African customs union operations, economic classification of government expenditure, functional classification of government expenditures, outstanding government domestic debt by instrument and holder, monetary survey, assets and liabilities of central and commercial banks, balance of payments, public and publicly guaranteed external debt outstanding, direction of trade, composition of recorded exports, and summary of the tax system are listed.